Remote Sensing data for the investigation of geo-hazard: EO4GEO project and the knowledge sharing challenges. Issue 1 (June 2020) - Cipolloni, C.; Comerci, V.; Delfini, C.; Ferrigno, F.; Guerrieri, L.; Leoni, G.; Spizzichino, D.; Ventura, R.
Abstract: The improved capabilities of Remote Sensing in data acquisition, analysis and implementation of standardized products lead decision makers and managers to a better understanding and assessment against geo-hazard. But since geo-hazard pose potential risks to people, assets and the environment the better knowledge to deal with the huge amount and the high quality of Earth Observation data is required. EO4GEO Project represents the latest challenge to define a standard methodology for the creation of integrated application using EO data and services to carry out geo-hazard risk monitoring, assessment and mitigation options.